Discourse on the Application of Dwangsom on Execution Court Decisions: A Comparison with Netherlands and France - Khaliza Fauzi, Maghfira Nur; Erliyana, Anna (Constitutionale, 2024)
The classic problem in resolving State Administration disputes boils down to the process of implementing decisions by the parties, which in practice still does not fully meet the expectations of justice seekers. If the decision is not implemented, the State Administrative Court (PTUN) imposes administrative sanctions / coercive measures against the losing party, which can be in the form of sanctions for forced payment of money (dwangsom), in order to increase the executable power of the decision. Normally, the same as the General Court, even though currently there are not many cases, it is still a problem. Article 116 paragraph (4) of the PTUN Law regulates the mechanism for coercive measures against the execution of PTUN decisions, but it is still interpreted as containing a "rechtsvacuum". This research uses normative legal research methods through literature study, and uses descriptive analysis with deductive and comparative methods. The results of the research show that the emergence of discourse on the application of dwangsom is interpreted as a means of psychological coercion against the losing parties in order to order them to comply with the ruling. If we refer to the comparison of the French and Dutch State Administrative Court justice systems, in the Administrative Justice system in France, if the government does not implement decisions that are its obligations, then it can be subject to astreinte/dwangsom, likewise in the Netherlands, the longer the decision of the administrative justice body is not implemented, the greater the burden of dwangsom that must be borne by TUN officials.